Uji Aktivitas Antioksidan dan Inhibisi Enzim alfa-Amilase Nano Ekstrak Kulit Buah Semangka (Citrullus lanatus (Thunb.) Matsum & Nakai): Antioxidant and alpha-Amylase Inhibitory Activities of Nano Extract From Watermelon Rind (Citrullus Lanatus (Thunb.) Matsum & Nakai) - Indriyani, Puspa; Rahmasari, Khusna Santika; Wirasti, Wirasti; Slamet, Slamet (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2025)
Watermelon rind (albedo) contains secondary metabolites such as alkaloids, flavonoids, saponins, tannins, as well as vitamins, minerals, lycopene, and citrulline, which have potential as antioxidants and regulators of glucose metabolism. This study aimed to determine the antioxidant activity and ?-amylase enzyme inhibition of watermelon rind extract and nano-extract. The extract was prepared using the maceration method with 96% ethanol, while the nano-extract was produced through ionic gelation. Antioxidant activity was tested using the FRAP method with UV-Vis spectrophotometry, while enzyme inhibition was measured using a microplate reader. The extract yield obtained was 14.30%. Nano characterization showed a transmittance percentage of 97.56 ± 0.05, particle size of 418.63 nm ± 1.06, polydispersity index of 0.622 ± 0.03, and zeta potential of 46.29 mV ± 0.11. The IC50 values for antioxidant activity of the extract and nano-extract were 81.46 µg/mL ± 0.23 and 62.88 µg/mL ± 0.036, respectively, while the IC50 for ?-amylase inhibition was 59.17 µg/mL ± 1.79 and 43.51 µg/mL ± 1.59. The nano-extract was proven to enhance both activities. Keywords: FRAP, Nano Extract of Watermelon Rind, ?-amylase enzyme Abstrak Kulit semangka (albedo) mengandung senyawa metabolit sekunder seperti alkaloid, flavonoid, saponin, tanin, serta vitamin, mineral, likopen, dan citrulline yang berpotensi sebagai antioksidan dan pengatur metabolisme glukosa. Penelitian ini bertujuan mengetahui aktivitas antioksidan dan inhibisi enzim ?-amilase dari ekstrak dan nano ekstrak kulit semangka. Ekstrak dibuat dengan metode maserasi menggunakan etanol 96%, sedangkan nano ekstrak melalui gelasi ionik. Aktivitas antioksidan diuji dengan metode FRAP menggunakan spektrofotometri UV-Vis, sedangkan inhibisi enzim diukur dengan microplate reader. Rendemen ekstrak diperoleh 14,30%. Karakterisasi nano menunjukkan % transmitan 97,56 ± 0,05, ukuran partikel 418,63 nm ± 1,06, indeks polidispersitas 0,622 ± 0,03, dan zeta potensial 46,29 mV ± 0,11. Nilai IC50 antioksidan ekstrak dan nano ekstrak masing-masing 81,46 µg/mL ± 0,23 dan 62,88 µg/mL ± 0,036, sedangkan IC50 inhibisi enzim ?-amilase 59,17 µg/mL ± 1,79 dan 43,51 µg/mL ± 1,59. Nano ekstrak terbukti meningkatkan kedua aktivitas tersebut. Kata Kunci: FRAP, Nano Extract of Watermelon Rind, Enzim ?-Amilase